Evidence of a reduction in cloud condensation nuclei activity of water-soluble aerosols caused by biogenic emissions in a cool-temperate forest - Astrid Müller (Nature Portfolio, 2017)
Abstract Biogenic organic aerosols can affect cloud condensation nuclei (CCN) properties, and subsequently impact climate change. Large uncertainties exist in how the difference in the types of terrestrial biogenic sources and the abundance of organics relative to sulfate affect CCN properties. For the submicron water-soluble aerosols collected for two years in a cool-temperate forest in northern Japan, we show that the hygroscopicity parameter κCCN (0.44 ± 0.07) exhibited a distinct seasonal trend with a minimum in autumn (κCCN = 0.32–0.37); these κCCN values were generally larger than that of ambient particles, including water-insoluble fractions. The temporal variability of κCCN was controlled by the water-soluble organic matter (WSOM)-to-sulfate ratio (R2 > 0.60), where the significant reduction of κCCN in autumn was linked to the increased WSOM/sulfate ratio. Positive matrix factorization analysis indicates that α-pinene-derived secondary organic aerosol (SOA) substantially contributed to the WSOM mass (~75%) in autumn, the majority of which was attributable to emissions from litter/soil microbial activity near the forest floor. These findings suggest that WSOM, most likely α-pinene SOA, originated from the forest floor can significantly suppress the aerosol CCN activity in cool-temperate forests, which have implications for predicting climate effects by changes in biogenic emissions in future.